IMPLEMENTASI METODE CERITA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI KABUPATEN SAMBAS (Studi Kasus Pada Madrasah Ibtidaiyah Swasta Darul Ulum Matang Danau Kecamatan Paloh) - Aslan Aslan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
Implementation represent applying and execution with method of story. The method of story is activity by teacher in educating and learning student which utilized in history culture of Islam (SKI) subject to reach the target of in good study. Teacher in telling a story require to master some technics in telling a story so that taken a fancy to children. Membership had SKI teacher in Islamic Elementary Schools (MIS) Darul Ulum telling a story make student very like to listen story and its target is emphasized at message of story found on SKI subject. This research aim to know method of story implementation, factors influencing students and impact from method of story implementation in history culture of Islam subject. This research with approach qualitative the equivalent case study form intristik that is to study and comprehend and also see morely circumstantial about case that happened in Islamic Elementary Schools Private Sector Darul Ulum Matang Danau. The research instrument use observation, interview, documentation. Checking of authenticity data that is lengthening of taking part in, triangulation, utilize to get result of accurate. The result of this research, researcher find four finding. First, method of forwarding story to show emotion by teacher, make student to ask question non with emotion teacher itself. Second, existence of teacher say off the cuff expression which require to hinder by teacher. Third, SKI teacher very mastering of history items culture in Islam so that child very glad with history story culture of Islam. Fourth, teacher in telling a story less is mastering vernacular that is Sambas Ianguage of so that child in raising question of teacher cannot understand what asked the child in Sambas Ianguage, because history teacher culture of Islam non from area of sambas but java. As for result of able to be seen from effective domain, cognate, and student psycomotorik seen from student when strarting a lesson, after executing result and lesson of student value individually in following subject of history culture of Islam.